The viability of applying alternative dispute resolution processes in the Niger Delta conflict - Ogaji, Ofinjite Joy (2013)
As the resource related conflict in the Niger Delta area of Nigeria escalates at a furious pace, it is becoming clear that traditional means of dispute resolution (such as litigation and violence) are no longer applicable. Research has also shown that no method of dispute resolution can be efficient, equitable and administratively practicable without the collective effort of all parties involved; individuals, institutions and non-governmental organizations need to work together to develop a countrywide ability to design an effective conflict resolution system. While there is a perceived need for a viable dispute resolution process, to date, no concerted effort has been made to harness relevant experiences and build a network of practitioners skilled in the management of such conflicts. The emerging Alternative Dispute Resolution (ADR) methods (which do not involve litigation) may offer opportunities to resolve disputes in the Niger Delta region more effectively than litigation-based means. In view of this, this research assesses indigenous dispute resolution processes in terms of their potential applicability as alternative dispute resolution processes for the Niger Delta conflict. The review also provides insights into the criteria used to support decision making as it relates to choosing the most appropriate dispute resolution process. To do this, this research advocates a hybrid model (an integration of both customary indigenous process and westernised mediation process). The choice of a hybrid model is predicated on the assumption that the Niger Delta is a hub for investors, where both locals (indigenes) and outsiders (foreigners) interact and relate together in pursuit of a common goal. Experience at the grass roots level in one community may also provide guidance for conflict resolution at similar levels in other communities.